Technical efficiency of beef cattle farms in Peninsular Malaysia - Mohd Radzil, Razida Hanem; Hamzah, Hanny Zurina; Ahmad Sidique, Shaufique Fahmi; Samsudin, Anjas Asmara@Ab. Hadi (Human Resource Management Academic Research Society, 2023)
Beef cattle farming is a challenging business to operate locally because of its low performance. Different price of beef product around Peninsular Malaysia happens due to the various condition of beef sources in each state in Peninsular Malaysia. This research aims to investigate the technical efficiency of beef cattle farms and its determinants. Farm-level data from 334 beef cattle producers collected from August 2020 to February 2021 were analysed by Data Envelopment Analysis (DEA) for technical efficiency scoring and the determinants discovered by using Tobit Model regression. The results show only 28.78 per cent of the farms operates at a total score of 1.00 while 33.54 per cent of the farms score less than 0.50 in technical efficiency. Technically efficient farms depend on experiences, corporate networking, education, household income and natural breeding technique. The findings help the industry to upgrade the operation standard of the farm in Malaysia by promoting the usage of Artificial Insemination techniques for beef cattle breeding intensively and comprehensively, with the involvement of corporates body to invest in the industry as one of the gestures for supporting the food security agenda of the country. Besides, educated youth might be interested in joining this industry if training incentives are provided, tax reductions for agro-food producers and strong support groups with authority.